Organizational Citizenship Behavior in Employees of PT Port Indonesia Regional IV Makassar Branch - Nur Alifhia Muhammad; Ihyani Malik; Nasrulhaq Nasrulhaq (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is to find out how Organizational Citizenship Behavior on employees. PT Pelabuhan Indonesia Regional IV Makassar Branch. This type of research is qualitative research with a descriptive approach, the data source comes from primary data and secondary data using observation, interview and documentation techniques. The results of this study indicate that Organizational Citizenship Behavior exists in employees who work at PT Pelabuhan Indonesia Regional IV Makassar Branch from aspects 1) Altruism is a caring attitude, employees of PT Pelabuhan Indonesia Regional IV Makassar Branch are willing to help or replace colleagues who have problems, 2) Conscientious is an attitude of respect and awareness of responsibility, employees have realized what they should do, 3) Sportsmanship is an employee's sportive ness, employees who work can always tolerate the obstacles they face, 4) Courtesy is an employee attitude who always maintain relationships with others, employees always avoid conflict, both to colleagues and especially to superiors, 5) Civic Virtue is an attitude of employee participation, employees always follow all the agendas at PT Pelabuhan Indonesia Regional IV Makassar Branch.